2015
DOI: 10.1111/nhs.12250
|View full text |Cite
|
Sign up to set email alerts
|

An Australian mixed methods pilot study exploring students performing patient risk screening

Abstract: Clinical placement shortages and rising costs have created demand to provide low-resource, high value student learning opportunities. Malnutrition screening provides a vehicle for achieving this. A mixed methods explanatory sequential intervention study investigated time costs, and students' perceptions of preparedness after performing routine patient screening tasks, as well as students' overall views on their feelings of confidence and preparedness when commencing their first clinical placements. Pre-clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…A total of 68 studies met the inclusion criteria and were included in this review . Fifty‐seven studies were identified from the search of 3779 records (Figure ) with an additional 11 studies identified through hand searching.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 68 studies met the inclusion criteria and were included in this review . Fifty‐seven studies were identified from the search of 3779 records (Figure ) with an additional 11 studies identified through hand searching.…”
Section: Resultsmentioning
confidence: 99%
“…8,10−12 Such SBLEs allow student practice without risk to patient safety 1,13,14 while promoting the development of student professionalism and resilience. 15 Within university-based education of health professionals, SBLEs are applied to increase student preparedness 2,16 and perceived confidence to perform on clinical placement 3,4 and as an assessment tool. 5,6 Simulation-based learning experiences can offer on-demand scenarios and purpose-developed cases to provide learners with experiences they may not otherwise encounter because of the limitations of clinical placement.…”
Section: Introductionmentioning
confidence: 99%
“…Of 7436 studies identified through database searching (Figure 2) and one additional study located through hand-searching of the reference lists, the final library consisted of 13 studies (Table 1). Nine [25,26,27,28,29,30,31,32,33] were quantitative studies, one [34] was a mixed methods study, and three [35,36,37] were qualitative studies.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 reports the key study characteristics of included studies. Literature was identified from the United States (US) and Canada, Australia, United Kingdom (UK), and Japan [25,26,27,28,29,30,31,32,33,34,35,36,37]. Students usually were identified as being in the later years of nutrition and dietetics programmes.…”
Section: Resultsmentioning
confidence: 99%